Preparation and Denitrifying Performance of V2O5-MoO3/TiO2-CeO2/H-Mordenite - Xue, Rujun; Chen, Chunyang; Wang, Qingchao; Zhou, Min; Chen, Shufen (Asian Journal of Chemistry, 2014)
With MoO3 as additive, V2O5 coatings was loaded to H-mordenite zeolite-TiO2 composite carrier to prepare V2O5-MoO3/ TiO2-CeO2/HM as NOx SCR catalyst. X-Ray diffraction, N2 adsorption-desorption and NH3 temperature programmed desorption (NH3-TPD) techniques were used to characterize the structure, surface area, acidity of the catalyst. Denitration performance of the catalyst was investigated using fixed-bed micro-reactor. The effect of V2O5 content on denitrification performance was studied extensively. Experimental results show that H-mordenite zeolite is beneficial to increase the specific surface area of the TiO2 support and improve V2O5 dispersing on the carrier in a monolayer state. The catalyst with 8 % V2O5 load displays optimal denitration performance. When the V2O5 load ³ 8 % V2O5, the catalytic activity decrease. MoO3 has help to vanadium-base catalyst and the denitration performance of the V2O5/CeO2-TiO2/HM with MoO3 additive increased and NO conversion reached to 92 %.